2015
DOI: 10.1039/c5nr03791c
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-sensitive tandem colloidal quantum-dot photodetectors

Abstract: The solution-processed PbSe colloidal quantum-dot (CQD) infrared photodetector with tandem architecture is proposed to address the high dark current issue. The electrical transport mechanism in tandem has been fundamentally changed in which the recombination of carriers at an intermediate layer becomes dominant rather than carriers hopping between nearest neighbors in CQD materials. As a result, the tandem photodetector exhibits ultra-high detectivities of 4.7 × 10(13) Jones and 8.1 × 10(13) Jones under 34 μW … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Generally, it is advantageous of manufacturing photodetectors with solution-processed colloidal nanocrystals as active materials in contrast to that made from solid-phase epitaxial routes [10] since that the solution-processed nanocrystals can be facilely prepared at relatively low reaction temperature and have good mechanical flexibility, resulting in superior compatibility with diverse substrates such as silicon wafer, glass and even printing paper. Up to now, a variety of photodetectors based on solution-processed PbSe and its related compounds/derivatives show prominent photoresponse in visible, NIR and MIR regions [11][12][13][14][15][16][17], and it is found that PbSe/PbS core/shell tetrapods-based photodetectors present with an optimal responsivity of 11.9 A•W −1 [18], while most of the photodetectors have relatively low response time from several seconds to dozens of milliseconds due to persistent photoconductivity behavior, which cannot meet the requirements for high-frequency and fast-speed optical devices.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, it is advantageous of manufacturing photodetectors with solution-processed colloidal nanocrystals as active materials in contrast to that made from solid-phase epitaxial routes [10] since that the solution-processed nanocrystals can be facilely prepared at relatively low reaction temperature and have good mechanical flexibility, resulting in superior compatibility with diverse substrates such as silicon wafer, glass and even printing paper. Up to now, a variety of photodetectors based on solution-processed PbSe and its related compounds/derivatives show prominent photoresponse in visible, NIR and MIR regions [11][12][13][14][15][16][17], and it is found that PbSe/PbS core/shell tetrapods-based photodetectors present with an optimal responsivity of 11.9 A•W −1 [18], while most of the photodetectors have relatively low response time from several seconds to dozens of milliseconds due to persistent photoconductivity behavior, which cannot meet the requirements for high-frequency and fast-speed optical devices.…”
Section: Introductionmentioning
confidence: 99%
“…According to the group, this performance was achieved by addressing the dark current by introducing the intermediate Poly-TPD (poly(N,N 0 -bis-4-butylphenyl-N,N 0bisphenyl)benzidine) layer (IL), which fundamentally transitions the carrier transport mechanism from the previously dominant nearest-neighbor hopping (NNH) to recombination of carriers at the IL interface. 130 Sulaman et al reported a tandem broadband photodiode composed of a stack of ITO/PEDOT:PSS/CsPbBr3:PbS0.4Se0.6/ ZnO/PVK/CsPbBr3:PbS0.4Se0.6/ZnO/Au with a maximum D* of 6.8 Â 10 13 Jones with an R of 27 A W À1 illuminated with a 980 nm wavelength using a 57.8 mW source. 131 While this performance was impressive, it was further improved by introducing a 50 nm PMMA dielectric between the ZnO and PVK layers.…”
Section: View Article Onlinementioning
confidence: 99%
“…While PbS CQD thin films can and are being used for devices such as photodetectors, their range of operation is limited to wavelengths shorter than 2 µm. [ 11,12 ] PbSe CQDs offer the potential to extend the range of operation of optoelectronic devices beyond that limit, and photodiodes based on PbSe have already been demonstrated. [ 12–16 ] The growth of PbSe quantum dots, primarily of smaller size grains, has already been reported in a number of publications.…”
Section: Figurementioning
confidence: 99%
“…[ 11,12 ] PbSe CQDs offer the potential to extend the range of operation of optoelectronic devices beyond that limit, and photodiodes based on PbSe have already been demonstrated. [ 12–16 ] The growth of PbSe quantum dots, primarily of smaller size grains, has already been reported in a number of publications. [ 6, 17–21 ] In this work we studied a comprehensive range of growth conditions and resulting optical properties of large (absorption beyond 2 µm) CQD of PbSe.…”
Section: Figurementioning
confidence: 99%